Genetics for dummies - Robinson, T. R. [ (Tara Rodden)] (For dummies, 2010)
A practical guide that gets you up to speed on all the fundamentals and the most recent discoveries in genetics, in easy-to-understand terms. You?ll see how people are applying genetic science to fight disease, develop new products, solve crimes-- and even clone cats!